Examination of the Relationship Between Attitudes Towards Healthy Nutrition and Mental Toughness of Athletes in Different Branches - Ozsari, Arif; Kara, Nuriye Seyma; Kara, Mehmet (Progress in Nutrition, 2022)
Study Objectives: This study aimed to examine the relationship between attitudes towards healthy nutrition and mental toughness of athletes (aged   = 17.77 ± SD= 8.88,  122  females, 245 males, a total of 367 ) in different branches. Method: Attitude scale for healthy nutrition, mental toughness scale, and personal information form were used to collect data. Confirmatory factor analysis (CFA) was administered for these scales. In addition to descriptive statistics, correlation and regression analyzes were performed under the relational model.  Result: It was concluded that there was a positive relationship between knowledge on nutrition and positive nutrition with mental toughness. Conclusion: Athletes’ knowledge on nutrition and their attitudes towards positive nutrition increase regarding their attitudes for healthy nutrition, their mental toughness will also increase.